Le Régime Alimentaire Du Poisson Sandre Sander lucioperca Peuplant Le Barrage Bouhamdane (Guelma) - Amairia Fatiha; Mellouk Hania (My University, 2021)
This study deals with the diet of the Sandre Sander lucioperca of Bouhamdane dam Lake inGuelma. stomach contents of 363 individuals captured monthly (december 2019-november 2020) ranging in sizefrom 25 to 44,5cm were analyzed. The qualitative and quantitative composition of the diet (Vacuity, relativeabundance, dietary index) is analysed according to the size of the fish and the sampling season. The averageannual vacuity is estimated at 70,79% and varies significantly depending on the seasons, especially in spring andsummer (reproductive period). the food composition shows that the Pike perch iscarnivorous, and its foodspectrumconsistsmainlyoflablettefish(Ar=97%)andshrimp(Ar=3%). ----------------------------------------------------------------------------------------------- تتناول هذه الدراسة النظام الغذائي لطائر Sandre Sander lucioperca ببحيرة سد بوحمدان بولاية قالمة. تم تحليل محتويات معدة 363 فردًا تم التقاطها شهريًا (ديسمبر 2019 - نوفمبر 2020) وتتراوح أحجامها من 25 إلى 44.5 سم. يتم تحليل التركيب النوعي والكمي للنظام الغذائي (الفراغ، الوفرة النسبية، المؤشر الغذائي) وفقًا لحجم الأسماك وموسم أخذ العينات. ويقدر متوسط ​​الخلو السنوي بـ 70,79% ويختلف بشكل كبير باختلاف الفصول وخاصة في فصلي الربيع والصيف (فترة التكاثر). يُظهر التركيب الغذائي أن سمك الفرخ لاحم، ويتكون طيفه الغذائي بشكل أساسي من الأسماك المسطحة (Ar=97%) والروبيان (Ar=3%). --------------------------------------------------------------------------------------------- Cette étude traite le régime alimentaire duSandre Sanderlucioperca de barrage Bouhamdane àGuelma.les contenus stomacaux de 363 individus capturés mensuellement (décembre 2019-novembre 2020) detaille allant de 25 à 44,5cm, ont été analysés.la composition qualitative et quantitative du régime alimentaire(Vacuité, abondance relative, indice alimentaire) est analysée en fonction de la taille des poissons et de la saisonde prélèvement. La vacuité moyenne annuelle estimée à 70,79% et varie sensiblement en fonction des saisons,notamment en printemps et été (période de reproduction).la composition alimentaire montre que le Sandre estcarnivore, et son spectre alimentaire se compose essentiellement de poisson lablette (Ar=97%) et de crevette(Ar=3%).